Effects of fear of missing out on inhibitory control in social media context: evidence from event-related potentials - Xu, Yang; Tian, Yu (Frontiers in Psychiatry, 2023)
The present study aimed to investigate the impact of Fear of Missing Out (FoMO) on inhibitory control in social media context. The present study used a two-choice oddball task combined with event-related potentials (ERPs) technology to measure inhibitory control. Based on the Fear of Missing Out scale, participants with varying degrees of FoMO were recruited to complete two studies. A total of 78 participants in Study 1 completed a two-choice oddball task (stimuli "W" or "M"). The results showed that FoMO did not have a significant impact on general inhibitory control at both the behavioral and electrophysiological levels. To further examine the effect of FoMO in a social media context. In Study 2, 72 participants completed a modified two-choice oddball task with three types of pictures (high and low social media-related, neutral). The behavioral results revealed that as FoMO scores increased, inhibitory control decreased. ERPs analysis revealed that with higher FoMO scores, social media-related pictures elicited larger N2 amplitude and smaller P3 amplitude, but not for neutral pictures. This suggests that FoMO undermines inhibitory control by consuming more cognitive resources in the early conflict detection stage and leading to insufficient cognitive resources in the later stages of the inhibitory process. These findings suggest that FoMO can undermine inhibitory control in social media context. Considering the indispensable use of social media in the digital age, addressing and understanding the influence of FoMO on inhibitory control could be essential for promoting healthy digital behaviors and cognitive functions.